Alternaria arborescens, IDENTIFIED AS A LEAF NECROSIS PATHOGEN OF Vigna radiata IN PAKISTAN - Sobiya Shafique; Shazia Shafique; Ume Attia; Mariam Zameer (Journal of Animal and Plant Sciences, 2024)
Vigna radiata (mung bean) is a most cultivated legume crop having high nutritive and clinical value. A survey was accompanied to isolate leaf spot pathogen from mung bean plants. Infected leaf samples were collected and a novel pathogen, Alternaria arborescens was isolated and identified on morphological and molecular basis. Molecular identification was done using nucleotide sequence analysis of rDNA internal spacer sequence (ITS), partial glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and elongation factor (EF) regions. Morphological characters demonstrated grayish-black, woolly, concentric rings on Malt Extract Agar (MEA) plates. The conidiophores were well defined; septate with terminal and sub-terminal branches having tan to brown, short ovoid or ellipsoid, and 7-11 µm sized conidia with transverse septation. In molecular characterization, BLAST analysis of the rDNA-ITS region of the pathogen, A. arborescens exhibited maximum (99%) homology with other A. arborescens GenBank strains. Similarly, 100% homology was found with partial glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and translation elongation factor. Afterward, Koch’s pathogenicity aptitude of the identified pathogen was confirmed by the occurrence of the same disease symptomology and re-isolation of identical organisms from artificially inoculated leaves in the in vitro and in vivo trials. The study signifies the novel documentation of A. arborescens as a leaf spot pathogen of mung bean in Pakistan. The manifestation of this pathogen could result in a serious economic impact on mung bean or might be a possible pathogen of other pulse crops if not managed in time.
Keywords: Alternaria arborescens; Genetic characterization; Leaf spot disease; Morphology; Vigna radiata